Evaluation of protein: creatinine ratio on random urine samples in assessment of proteinuria - Anchinmane, Vyankatesh T.; Sankhe, Shilpa V. (International Journal of Research in Medical Sciences, 2016)
Background: Significant proteinuria (>300mg/day) may indicate the presence of important renal disease. Quantitative estimation of urinary protein over 24 hours is the gold standard test for detection of proteinuria. However, 24 hours urine collection method is inconvenient and cumbersome to patients. The present study was undertaken to determine diagnostic accuracy of random urine protein: creatinine ratio for the diagnosis of proteinuria among patients with renal diseases. Methods: The prospective study was done in 200 nephropathy cases. The 24 hours urinary protein test used as gold standard test and compared with their random urine sample protein: creatinine ratio (cut off >0.3). The data analyzed for sensitivity, specificity and accuracy of random urine sample protein: creatinine ratio test. Results: Random urine sample protein: creatinine ratio test showed sensitivity, specificity and accuracy of 95.6%, 94.4% and 95.5% respectively Conclusions: The convenient and accurate protein: creatinine ratio method on random urine samples is reliable method for estimation and screening the proteinuria cases over quantification of proteinuria by collection of 24 hours urine samples and hence, a wider application of this method is recommended.